Green Finance Literacy for Community Services in Purwakarta, Indonesia - Purba, Yosephina Endang; Leon, Farah Margaretha; Martadisastra, Dedie Supriado (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
This community service program aimed to enhance green finance literacy by introducing sustainability concepts and green financial strategies to Micro, Small, and Medium Enterprises (MSMEs) and students at Yayasan Global Nubuah Insani (GCNI), Purwakarta, Indonesia, in order to support the adoption of environmentally responsible business practices. The program employed a community-based participatory approach, involving 60 MSME actors and senior high school students. The intervention was delivered through structured workshops consisting of sustainability education, green finance lectures, case study discussions, and group reflections. Program effectiveness was evaluated using a pre-test and post-test design supported by qualitative observations and participant feedback. The program was implemented through interactive lectures, case discussions, and green business planning simulations. Assessments showed a 45% increase in participants’ understanding of green finance principles, particularly in identifying environmentally friendly business practices and accessing green funding schemes from governmental and international institutions. The participants also demonstrated a proactive attitude toward integrating sustainability into their operations. This initiative showcases the potential for academic institutions to contribute meaningfully to local awareness of the Sustainable Development Goals (SDGs) and the green economy transition.